Antimicrobial Bioactive Compounds of Snail Seromucoid as Biological Response Modifier Immunostimulator - AGNES SRI HARTI; NONY PUSPAWATI; RAHAJENG PUTRININGRUM (Microbiology Indonesia, 2019)
Anti-microbial bioactive compounds from snail (Achatina fullica Ferussac) contained in snail seromucoid. It contains bioactive compounds such as glycans, peptides, glycopeptides, and chondroitin sulfate which can function as biological response modifiers (BRM) immunostimulators. Immunostimulators are compounds that can increase cellular immune responses in various ways, namely increasing the number and activity of T cells, NK cells, and macrophages and releasing interferons and interleukin. Immunostimulators are compounds that can increase cellular immune responses in various ways, namely increasing the number and activity of T cells, NK cells, macrophages and releasing interferons and interleukins.The purpose of this study was to analyze antimicrobial bioactive seromucoid compound of snail (Achatina fullica Ferrusac) as biological response modifiers (BRM) immunostimulators. The research methods based on experimental laboratory results with research stages including snail seromucoid isolation; antimicrobial activity; characterization physicochemical and profile of snail seromucoid proteins. The results of antimicrobial activity showed that 100% seromucoid concentrations had MIC (Minimal Inhibition Concentration) in Staphylococcus aureus, Candida albicans, and Pseudomonas aeruginosa. The physicochemical examination results showed specific gravity of 1.010; pH 8, -1 -1 -1g lucose 16 mg dL ; 9 mg dL cholesterol; protein 2.8 mg dL and negative heavy metals (Pb, Cu, Hg, Al). The results of the analysis of protein profiles showed that there were 3 subunits of proteins, range from 55 to 72 kDa and 1 specific protein sub unit of 43 kDa which was thought to be antimicrobial and biological response modifiers (BRM) immunostimulators.